2019
DOI: 10.1177/2158244019854639
|View full text |Cite
|
Sign up to set email alerts
|

Online Consumer Typologies and Their Shopping Behaviors in B2C E-Commerce Platforms

Abstract: Consumer behavior in e-commerce platforms is one of the extensively researched area. Numerous studies in this field assessed consumer online shopping behavior from various aspects. However, literature review showed that most of the conducted studies do not carry out market segmentation analysis while accessing shopping behavior of online consumers. Therefore, the general conclusions made by these studies about consumer attitude, behavior, and decision-making process might not reflect actual behaviors of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 74 publications
(202 reference statements)
1
33
0
Order By: Relevance
“…Meanwhile MHI also provides booths in traditional markets to help 22.4-million senior citizens coping with stairs and slippery floors so they can have the same services offline and maintain their existing sociocultural interactions in traditional markets 2) through customer orders and reviews, to encourage 12.6-million traditional market small traders starting and upgrading their products and services into customer-oriented ones 3) and in the end, to be hand in hand with 35.7 farmers and fishermen distributing crops to the right demands according to customers' preferences 4) by giving everyday-fresh, ready-to-cook and right portion of ingredients according to customers' chosen recipes, to help customers having better food planning and encouraging healthy customized balance diets 5) to sustain the economy of traditional small traders in collaboration with local market managements, online delivery services, bank and e-wallet, food technology institutions and industries, farmers and governmental institutions (Figure 2, middle image). Other research also showed that in all customer segments, when customers not only perceived online shopping useful but also compatible with their lifestyle -as smart phone users-they would build favourable tendency toward online shopping [9]. MHI as an online transaction process also has a promising prospect as shown in 5 methods (People, Place, Process, Promotion, Physical Evidence) to improve traditional market.…”
Section: Resultsmentioning
confidence: 96%
“…Meanwhile MHI also provides booths in traditional markets to help 22.4-million senior citizens coping with stairs and slippery floors so they can have the same services offline and maintain their existing sociocultural interactions in traditional markets 2) through customer orders and reviews, to encourage 12.6-million traditional market small traders starting and upgrading their products and services into customer-oriented ones 3) and in the end, to be hand in hand with 35.7 farmers and fishermen distributing crops to the right demands according to customers' preferences 4) by giving everyday-fresh, ready-to-cook and right portion of ingredients according to customers' chosen recipes, to help customers having better food planning and encouraging healthy customized balance diets 5) to sustain the economy of traditional small traders in collaboration with local market managements, online delivery services, bank and e-wallet, food technology institutions and industries, farmers and governmental institutions (Figure 2, middle image). Other research also showed that in all customer segments, when customers not only perceived online shopping useful but also compatible with their lifestyle -as smart phone users-they would build favourable tendency toward online shopping [9]. MHI as an online transaction process also has a promising prospect as shown in 5 methods (People, Place, Process, Promotion, Physical Evidence) to improve traditional market.…”
Section: Resultsmentioning
confidence: 96%
“…PEU defines the degree; a user considers that technology usage can be effort-free whereas, PU defines to the degree a user thinks that technology usage will advance one's job execution or productivity. TAM study has discovered that together, PEU and PU are significant constructs of users' acknowledgment, implementation, and utilization conduct [8], [17], [54], [55].…”
Section: Conceptual Framework and Hypotheses A Conceptual Framementioning
confidence: 99%
“…The perceived playfulness (hedonic motivation) has a high positive and robust association with information systems usage and supports in determining usage acceptance for digital technologies [8], [26]. ''Hedonic motivation'' defines the pleasure resulting from technology usage and a vital construct of consumer's acceptance to use a technology [65]- [68].…”
Section: Conceptual Framework and Hypotheses A Conceptual Framementioning
confidence: 99%
See 1 more Smart Citation
“…The posting of updates and checking profiles on one or more social network sites (SNSs) in daily life have become part of many individuals [1]. Internationally, the number of online users has increased, so the extent of internet consumers and the audience has also increased [2]. Within the 21st century, it is expected that firms would significantly integrate novel technologies to attain sustainability and competitive advantage [3].…”
Section: Introductionmentioning
confidence: 99%